The discovery of pyridinium 1,2,4-triazines with enhanced performance in bioconjugation reactions - Siegl, Sebastian J; Dzijak, Rastislav; Vázquez, Arcadio; Pohl, Radek; Vrabel, Milan (Chemical science, 2017)
1,2,4-Triazines have recently been identified as versatile dienes participating in the inverse electron-demand Diels-Alder reaction with strained dienophiles. However, their widespread utility in bioconjugation reactions is still limited. Herein, we report a systematic study on the reactivity of various 1,2,4-triazines with trans-cyclooctenes showing that the structure of both the triazine and the dienophile significantly affect the reaction rate. Our kinetic study led to the discovery of novel cationic 1,2,4-triazines with superior properties for bioconjugation reactions. We have developed an efficient method that enables their late-stage functionalization and allows for easy access to various useful heterobifunctional scaffolds. In addition, these charged dienes form unprecedented fluorescent products upon reaction with trans-cyclooctenes and can be used for fluorogenic labeling of subcellular compartments in live cells.